Social entrepreneurship: an alternative for solid waste management: a case study of Majlis Perbandaran Kota Samarahan (MPKS), Sarawak. - Sulzarina Mohamed. (2017)
A case study was done at Majlis Perbandaran Kota Samarahan (MPKS), Sarawak regarding Social Entrepreneurship as an alternative solution for Solid Waste Management (SWM) in Samarahan, Sarawak. The objectives of the study were to understand and identify the aspects of social issues that closely associated with SWM and at the same time surveying potential for social entrepreneurship to build their business model. Therefore, an analysis using Porter’s Five Forces Model on the business model had concluded that moderate opportunity and risks for the social entrepreneur to involve in this industry. However, the business prospect has shown a positive sign for this business to prosper in the future. The case study shown that social entrepreneur in Samarahan had a wide window of opportunity to use the municipal solid waste as a supply of their business opportunity by implement the unique process such as 3R and Anaerobic digestion. This approach provides the solution by decreasing the aggregate of solid waste in the environment, developing employment opportunities, minimize the health risk in society and gives sustainable source of heat and electricity. Besides that, social entrepreneurs on SWM in Samarahan are failing to meet the conventional necessity and therefore failing to acquire enough earnings for their business to survive. It is suggested that they need to instil innovation as their business drivers in order to compete in the business. It was also found that overall industry of SWM is led by MPKS and it is crucial for MPKS to provide circumstances for entrepreneurs and social entrepreneurs and optimize the resources on hand in Samarahan. The lack of existing facilities, knowledge and concerns about recycling contributes to the problem of waste in Samarahan. However, MPKS has the power to play their cards right to ensure social entrepreneurship as an alternative solution to SWM in Samarahan.